HUBUNGAN SOSIAL EKONOMI DENGAN STATUS GIZI PADA REMAJA PUTRI DI SMPN I BARITO TUHUP RAYA - Rumi Amanda; Elvine Ivana Kabuhung; Nita Hestiyana; Dwi Sogi Sri Redjeki (Jurnal Kesehatan, 2025)
Adolescent girls are considered a vulnerable group to nutritional problems, both undernutrition and overnutrition. The socioeconomic status of the family influences adolescents’ dietary patterns and nutrient intake. However, the relationship between socioeconomic conditions and nutritional status is not always linear, particularly in rural areas with limited food access. This study aimed to determine the extent of the relationship between socioeconomic status and the nutritional condition of adolescent girls at SMPN 1 Barito Tuhup Raya. An analytical observational design with a cross-sectional approach was employed. The sample consisted of 54 adolescent girls selected using a total sampling technique. Socioeconomic status was categorized based on family income (≤ or > IDR 3,500,000). Nutritional status was determined through the calculation of Body Mass Index (BMI). Data were analyzed using the Chi-Square test to examine the relationship between variables. The majority of respondents were from families with low socioeconomic status (59.3%) and had normal nutritional status (63%). Bivariate analysis revealed a significant relationship between socioeconomic level and nutritional condition (p = 0.027). Interestingly, adolescent girls from lower-income families had a higher proportion of normal nutritional status compared to those from higher-income families. The findings indicate that socioeconomic background has a meaningful association with the nutritional condition of adolescent girls. However, family income is not the only determining factor; dietary patterns, eating habits, nutrition literacy, and lifestyle also contribute to adolescents’ nutritional status.   Abstrak: Remaja putri termasuk kelompok yang rentan mengalami masalah gizi, baik gizi kurang maupun gizi lebih. Status sosial ekonomi keluarga turut memengaruhi pola konsumsi dan asupan gizi remaja. Namun, hubungan antara kondisi sosial ekonomi dan status gizi tidak selalu bersifat linier, terutama di wilayah pedesaan dengan keterbatasan akses pangan. Penelitian ini dilakukan untuk mengetahui sejauh mana status sosial ekonomi berhubungan dengan kondisi gizi remaja putri di SMPN 1 Barito Tuhup Raya. Desain penelitian yang digunakan adalah observasional analitik engan rancangan potong lintang (cross-sectional). Sampel berjumlah 54 remaja putri yang dipilih dengan teknik total sampling. Data status sosial ekonomi dikategorikan berdasarkan pendapatan keluarga (≤ atau > Rp3.500.000). Tingkat status gizi responden ditetapkan melalui perhitungan Indeks Massa Tubuh (IMT). Data dianalisis dengan menggunakan uji chi-square untuk mengetahui hubungan antarvariabel. Mayoritas responden tercatat berasal dari keluarga dengan kondisi sosial ekonomi rendah (59,3%) dan menunjukkan status gizi normal (63%). Hasil analisis bivariat menunjukkan terdapat hubungan signifikan antara tingkat sosial ekonomi dan kondisi gizi remaja (p = 0,027). Menariknya, remaja dari keluarga ekonomi bawah justru memiliki proporsi kondisi gizi normal yang lebih tinggi dibandingkan kelompok ekonomi atasHasil penelitian menunjukkan adanya hubungan yang bermakna antara latar belakang sosial ekonomi dan keadaan gizi remaja putri. Namun, pendapatan keluarga bukan satu-satunya faktor penentu. Pola konsumsi, kebiasaan makan, literasi gizi, dan gaya hidup turut memengaruhi status gizi remaja